2000
DOI: 10.1046/j.1360-0443.2000.9569017.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a scale measuring self‐efficacy of current and former smokers

Abstract: SEQ-12 is a valid and reliable scale, which has applications in both research and clinical settings. It can also produce input data for computer systems that generate counselling reports tailored to the characteristics of each individual smoker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
187
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(196 citation statements)
references
References 0 publications
6
187
0
3
Order By: Relevance
“…Short-term follow-up studies in adolescence have sought to describe the causal direction of this relationship, especially in the context of adolescent stress predicting the uptake of cigarette smoking (Byrne & Mazanov, 2003;Wills et al, 2002). Our results are consistent with the view that tobacco smoking may inhibit the development of self-efficacy or the confidence in one's ability to act in a given situation (Etter et al, 2000). As Parrott (1999) points out, because of its addictive nature, smoking becomes a highly overlearned behavior.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Short-term follow-up studies in adolescence have sought to describe the causal direction of this relationship, especially in the context of adolescent stress predicting the uptake of cigarette smoking (Byrne & Mazanov, 2003;Wills et al, 2002). Our results are consistent with the view that tobacco smoking may inhibit the development of self-efficacy or the confidence in one's ability to act in a given situation (Etter et al, 2000). As Parrott (1999) points out, because of its addictive nature, smoking becomes a highly overlearned behavior.…”
Section: Discussionsupporting
confidence: 80%
“…Elsewhere, we have estimated that the young smokers in our sample would have smoked on average about 25,000 cigarettes from the ages of 15-21 years; by age 32, for the 8 in every 10 who continued smoking daily, they would have smoked a staggering 66,000 cigarettes each (Welch & McGee, 2010). Perhaps 25% of these cigarettes were smoked in response to negative affect, including stress, worry, and boredom (Etter et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming some , but not all previous reports (Cheong et al, 2007), we found that preference for abrupt was associated with known predictors of abstinence such as motivation to quit and confidence in ability to quit (Etter et al, 2000;Peters et al, 2007). In addition, at baseline, time elapsed since the most recent relapse was 6 months shorter in those who preferred abrupt than in those who preferred gradual, suggesting that the former group made more frequent quit attempts.…”
Section: Discussionsupporting
confidence: 74%
“…We measured cognitive factors shown to be predictive of smoking abstinence in previous research, including motivation to quit (stages of change) [48], selfefficacy for achieving smoking cessation, and the participant's confidence in his ability to abstain from smoking in high-risk situations (Smoking SelfEfficacy Questionnaire (SEQ)) [49] and situational temptations to smoke (Smoking Situations Temptations Inventory (SST)) [50]. We also assessed for depression (CES-D) [51,52], anxiety (STAIT) [53], mindfulness (Freiburg Mindfulness Inventory (FMI)) [54], and physical self worth, attractiveness, physical strength, and condition (Physical Self Perception Profile Scale (PSPP)) [55].…”
Section: Original Researchmentioning
confidence: 99%